Interaction of a synthetic mitochondrial presequence with isolated yeast mitochondria: mechanism of binding and kinetics of import. - Roise, D (1992)
The mechanism of interaction of a presequence with isolated yeast mitochondria was examined. A synthetic peptide corresponding to a matrix-targeting signal was covalently labeled with a fluorescent probe. Binding of the presequence to the surface of the mitochondria and translocation of the presequence into the interior of the mitochondria could then be monitored directly in solution by measuring changes in the steady-state fluorescence of the attached fluorophore. The binding step was rapid and reversible. Quantitation of the binding under equilibrium conditions suggested that the initial association of the presequence with the surface of the mitochondria occurred by partitioning of the presequence directly into the lipid bilayer of the outer membrane. Subsequent translocation of the bound presequence into the mitochondria was monitored by measuring the rate of disappearance of presequences sensitive to digestion by added trypsin. The efficiency of translocation was high, and the rate of the translocation was dependent on the electrical potential across the inner membrane. At physiological concentrations of presequence, the rate displayed first-order kinetics with respect to the concentration of bound presequence and had a rate constant of 0.19 min-1 at 20 degrees C. Several kinetic models for the translocation of the presequence are presented that are consistent with the experimental results.